Four‐fold Channel‐Nicked Human Ferritin Nanocages for Active Drug Loading and pH‐Responsive Drug Release. (12th February 2018) - Ahn, Byungjun; Lee, Seong‐Gyu; Yoon, Hye Ryeon; Lee, Jeong Min; Oh, Hyeok Jin; Kim, Ho Min; Jung, Yongwon
Abstract: Human ferritins are emerging platforms for non‐toxic protein‐based drug delivery, owing to their intrinsic or acquirable targeting abilities to cancer cells and hollow cage structures for drug loading. However, reliable strategies for high‐level drug encapsulation within ferritin cavities and prompt cellular drug release are still lacking. Ferritin nanocages were developed with partially opened hydrophobic channels, which provide stable routes for spontaneous and highly accumulated loading of Fe II ‐conjugated drugs as well as pH‐responsive rapid drug release at endoplasmic pH. Multiple cancer‐related compounds, such as doxorubicin, curcumin, and quercetin, were actively and heavily loaded onto the prepared nicked ferritin. Drugs on these minimally modified ferritins were effectively delivered inside cancer cells with high toxicity.